Automotive electricity and electronics - Halderman, James D. 1943- (Pearson/Prentice Hall, 2005)
Designed specifically to correlate with the NATEF program and ASE certification tests, this comprehensive, up-to-date book covers all aspects of automotive electricity and electronics. It emphasizes diagnosis and troubleshooting, and features tech tips and diagnostic stories throughout. The complete learning package includes a multimedia CD ROM with illustrated power point slides, and a workbook containing activities also correlated to the NATEF task list. Both Theory and Diagnosis and Service are together in the one book format. Correlated to the NATEF task list - the book and workbook page numbers are listed in the NATEF correlation guides to make learning easier. Correlated to ASE Certification areas. Automotive technicians.